Soil contamination in urban squares and beaches by larvae of Strongyloides spp. and Hookworm in a tourist town in northeastern Brazil - Oliveira, Claudio Bruno Silva de; Cardoso, Anna Clara de Araújo; de Almeida, Lisianny Barbara Gomes Moreira; Fernandes, Luiz Pessoa; de Sousa, Ana Glória Barbosa Bezerra (South American Journal of Basic Education, Technical and Technological, 2021)
Helminth parasites are widely distributed in nature, they are known as humans and animals parasites. The hookworms and gender Strongyloides spp. cause skin, pulmonary and intestinal disease. In common, these helminths have infective forms present in the soil. In this sense, this study had as objective to evaluate the contamination of beaches and squares of Natal / RN (regions of great circulation of people and animals) by larvae of hookworms and Strongyloides spp. during the period between July 21, 2015, and February 1, 2016. The larvae were searched in regions of different humidity and luminosity. The soil samples were submitted to the Baermann-Moraes method to search for the larvae, which were then morphologically differentiated by light microscopy. The prevalence of human parasites in the six beaches was 16.7% while in 118 urban squares was 11.76%, in both sites the hookworms were more common. The parasites were found preferentially in hot and rainy periods. This is the first survey of the type carried out in the State and in an unprecedented way concludes that in Natal/RN there are squares and beaches contaminated by parasites that may represent a risk to human health, so are be necessary public health measures that act mainly on the adequate removal of sewage, trash and stray animals.